Survival and function following pharyngo-laryngo-oesophagectomy in Wales: a twelve-year case series. Issue 3 (29th March 2021) - Edwards, D R; Pope, L; Berry, S
Abstract: Objective: Treatment of locally advanced hypopharyngeal cancer can cause significant morbidity and late toxicity. Pharyngo-laryngo-oesophagectomy can achieve adequate surgical margins, but data on survival and functional outcome are limited, especially in Wales. This study aimed to describe mortality, morbidity and functional outcome following pharyngo-laryngo-oesophagectomy in a Welsh population. Method: This study was a retrospective case note review of pharyngo-laryngo-oesophagectomy cases in Wales over 12 years. Results: Fifteen patients underwent pharyngo-laryngo-oesophagectomy; all but one underwent gastric pull-up. Median survival and disease-free survival were 17 months (range, 2–53 months) and 14 months. Censored 3-month, 1-year and 3-year survival was 93, 71 and 50 per cent, respectively. Common Terminology Criteria for Adverse Events grading of long-term dysphagia was 1 in 58 per cent, 2 in 33 per cent and 3 in 8 per cent, and 87.5 per cent achieved a 'moderate' or 'good' voice rehabilitation. Conclusion: These results demonstrate favourable survival and reasonable functional outcome following pharyngo-laryngo-oesophagectomy, suggesting pharyngo-laryngo-oesophagectomy should be considered in all appropriate surgical candidates.